(untitled) (Journal of Geography and Environmental Management, 2016)
In the review the various indicators influencing safety of grain production are analyzed: the heavy metals (HM) and other substances polluting agricultural production. It is established that in hierarchy of indicators of agro ecological stability of grain the leading part is assigned to TM. The maximum-permissible concentration (MPC) for grain and products of its processing on studied polluting substances are given. It is shown that mechanisms of absorption, transport, a metabolism and TM distribution in bodies and fabrics are closely connected with specific and high-quality features of cultivars. Relevance of studying of HM resistance of cereals is considered in connection with the solution of problems of ecological and food safety of agricultural production for providing «green economy» of Kazakhstan.